The ecological approach to visual perception and the actor performance captured in the gaming landscape. Issue 1 (1st December 2012) - Delbridge, Matt
The use of Performance Capture techniques in the creation of games that involve Motion Capture is a relatively new phenomenon. To date, there is no prescribed methodology that prepares actors for the rigours of this new industry and as such there are many questions to be answered around how actors navigate these environments successfully when all available training and theoretical material is focused on performance for theatre and film. This article proposes that through a deployment of an ecological approach to visual perception we may begin to chart this territory for actors and begin to contend with the demands of performing for the motion captured gaming scenario.